Retrospective cohort of a decade of pediatric kidney transplant in a Brazilian state: Clinical profile, main complications, and outcomes. - Marina da Rocha Lordelo; Claudia Andrade Nunes; Mariana Araújo-Pereira; Beatriz Barreto-Duarte; Bruno B Andrade (PLoS ONE)
Pediatric kidney transplant is performed globally, although unevenly, with specific challenges in low-income countries with limited resources. We aimed to describe pediatric kidney transplantation in Bahia, a state located in one of the poorest regions in Brazil, and explore possible predictors of survival. This was a single-center retrospective cohort, and we included 101 pediatric kidney transplants performed between 2013 and 2022. There was no predominance of sex; the median age was 12 years old. Congenital anomalies of the kidney and urinary tract were the most common etiology of renal disease. 21 transplants were preemptive. Delayed graft function occurred in just over half of transplants. Patient survival rate was 96%, 96%, 89.1%, and 89.1% respectively at 1-year, 3-years, 5-years, and 10-years post-transplant. The overall graft survival rate was 80.2%, 76.9%, 66.8%, and 45.8% at 1-year, 3-years, 5-years, and 10-years post-transplant. Multivariate analysis of outcome predictors revealed that delayed graft function was a risk factor for graft survival in 5 years (adjusted HR 3.44 (1,18-10,05)). Pediatric kidney transplantation is a regionally feasible treatment, with good outcomes, although slightly inferior to those reported in the literature; efforts on reducing incidence in delayed graft function may improve graft survival.